FEATURES OF THE MANIFESTATION OF LONELINESS (Scientific journal of the Fergana State University, 2024)
Loneliness is a multidimensional phenomenon inherent in all social systems of society, the theoretical study of which goes back to ancient roots. The complexity ofphenomenon. That is, the individual as well as the social shell of human existence, full of contradictions, stems from the reflection of a sense of loneliness. The variety of ideas on this topic requires a wide range of research on this phenomenon based on social psychology. To this end, we conducted an empirical study to examine the subjective feeling of loneliness among students. This article systematically analyzes the results of the work carried out on our research. The study used the technique of “Studying the subjective feeling of loneliness”, developed by D.Russell, L.Peplo and M.Ferguson. According to the results of the survey of respondents, it was found that students consider objective, subjective, external, internal and situationally expressed features of loneliness to be significant. This indicatethat students are at an age full of strength in terms of ontogenetic development, they rationally assess the emotional states occurring in human nature. Consequently, students consciously choose or deny the feeling of loneliness depending on situational stimulus.